Simulation based engineering in fluid flow design - Rao, J. S. (Springer, 2017)
This volume offers a tool for High Performance Computing (HPC). A brief historical background on the subject is first given. Fluid Statics dealing with Pressure in fluids at rest, Buoyancy and Basics of Thermodynamics are next presented. The Finite Volume Method, the most convenient process for HPC, is explained in one-dimensional approach to diffusion with convection and pressure velocity coupling. Adiabatic, isentropic and supersonic flows in quasi-one dimensional flows in axisymmetric nozzles is considered before applying CFD solutions. Though the theory is restricted to one-dimensional cases, three-dimensional CFD examples are also given. Lastly, nozzle flows with normal shocks are presented using turbulence models. Worked examples and exercises are given in each chapter. Fluids transport thermal energy for its conversion to kinetic energy, thus playing a major role that is central to all heat engines. With the advent of rotating machinery in the 20th century, Fluid Engineering was developed in the form of hydraulics and hydrodynamics and adapted in engineering Schools across the world until recent times. With the High Performance Computing (HPC) in recent years, Simulation Based Engineering Science (SBES) has gradually replaced the conventional approach in Fluid Flow Design bringing Science directly into Engineering without approximations. Hence this SpringerBrief in Applied Sciences and Technology. This book brings SBES to an entry level allowing young students to quickly adapt to modern design practices.
Includes index.
Keywords: Computational fluid dynamics.; Fluid dynamics -- Mathematical models.; elektronické knihy; electronic books